Philosophical Groundings for Humanisation: a Critical Litterature Review in Brazil - Gomes Barbosa, Thiago; Pereira Miguel, Roberto; Claramonte Gallian, Dante Marcello (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
This article presents the results of a critical analysis based on literature review on the national concept, and proposals for humanizing the healthcare in the Brazil. From 389 articles collected in national databases, published between January/2002 and May/2012, 41 were analyzed, and categorized according to three specific theoretical frameworks: humanizing gnostic-perfectible solutions, social-perfectible and non-perfectible solutions. This categorization, based on the critical approach to the philosophical foundations of modernity,, shows that: 1) The vast majority of the proposals analyzed in humanization were not concerned with properly citing their philosophical basis; 2) This same majority ultimately based, albeit not explicitly, on the "perfectible" Modern anthropological perspective; 3) The minority of the most recent proposals analyzed began to point to the "social non-perfectible" view, directing new approaches to the humanization-problem of healthcare in Brazil.